LA DACTILOPINTURA EN EL DESARROLLO DE LA CREATIVIDAD DE LOS NIÑOS Y NIÑAS DE CINCO AÑOS DE LA UNIDAD EDUCATIVA SAN FELIPE NERI DE LA CIUDAD DE RIOBAMBA EN EL PERIODO 2018 – 2019 - Abarca Cazco, Cinthya Erika (2019)
The investigation is about THE DACTILOPINTURA IN THE DEVELOPMENT OF THE CREATIVITY OF THE CHILDREN AND GIRLS OF FIVE YEARS OF THE UNIT EDUCATIONAL SAN FELIPE NERI OF THE CITY OF RIOBAMBA UN THE PERIOD 2018-2019 .Its purpose is determining the importance of the development creative of the children and helping the visual-motor coordination , creative and imaginative expression, stimulating the children to use the finger painting symbolically their thoughts .Having an object of study the 24 children , where it was used as a technique the observation and as an instrument , the observation sheet that consists of fifteen indicators for the data collection .Its evidencing that the painting stimulates communication , creativity, sensitivity and increases the capacity of concentration , taking it as an aid before a treatment, expressing the emotion and feelings within an environment ,strengthening self-esteem and reinforcing confidence in the child so that he feels capable of carrying out the activities and is curious about them . The results obtained were analyzed and interpreted with their respective percentages where at end of the investigation, the main characteristic are establishing within the manifestations of the fingerprint that the child has visual when he reproduces patterns, favoring having directionality and striking techniques for the exercise of the activities presented to the child.